PENINGKATAN HASIL BELAJAR PESERTA DIDIK MELALUI MEDIA AUDIO VISUAL PADA MAPEL FIQIH KELAS VI A MIN 2 MUSI BANYUASIN - Rohila Rohila; M. Hasbi; Kemas Badaruddin; Eni Zahara (GURUKU, 2022)
Based on the results of initial observations, it was revealed that the use of media in MIN 2 Musi Banyuasin is sometimes still simple. Often just using conventional media or pictures found in textbooks. The impact that occurs makes students become bored, and less excited so that they become less interested in learning. This matter This causes some students to not reach the KKM target. So that the use of audio visual powerpoint media can be an alternative that can be used because it can make it easier for students to learn in an effort to understand the learning material so that the expected learning outcomes of participants learn can improve The purpose of this study was to determine whether through Audio Visual media can improve student learning outcomes on the subject of Fiqh class VI A MIN 2 Musi Banyuasin. Based on the results of research that has been carried out in class VI A MIN 2 Musi Banyuasin, the researchers concluded that Audio Visual media can used to improve student learning outcomes. It can be seen of increasing the average learning outcomes and learning completeness of Class Students VI A MIN 2 Musi Banyuasin for the academic year 2021/2022. In the first cycle the average value of the students was 76 and increased in the second cycle to 82.67. Completeness of learning outcomes in the first cycle was 73.33%, increased to 93.33% onlearning activities in cycle II